TEGANGAN MAKSIMUM DAN FAKTOR KEAMANAN PADA POROS ENGKOL DAIHATSU ZEBRA ESPASS BERDASARKAN METODE NUMERIK - Achmad Zainuri; . Sujita; Alam Lawe Popo (Universitas Wahid Hasyim, 2010)
The purpose of this study was to determine the maximum stress and safety factor on the crankshaft Daihatsu Zebra Espass based on numerical methods. Material is selected as the crankshaft material is AISI 1053 steel. This numerical method uses CATIA software program to determine the maximum stress based on Von Mises failure theory. Research procedure begins by measuring the dimensions of the crankshaft Daihatsu Zebra Espass, then draw and analyze. Results of analysis in the form of images that show the stress distribution that occurs in the elements of the crankshaft. From the analysis results can be concluded that the highest maximum stress occurred in the area of the crankshaft fillet into 4 at the position 360o angle of 86.5 MPa with the lowest safety factor of 4.22. Keywords: crank shaft, CATIA, maximum stress, safety factor.